2014
DOI: 10.2147/ijn.s58357
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium ion implantation on a micro/nanostructured titanium surface promotes its bioactivity and osteogenic differentiation function

Abstract: As one of the important ions associated with bone osseointegration, magnesium was incorporated into a micro/nanostructured titanium surface using a magnesium plasma immersion ion-implantation method. Hierarchical hybrid micro/nanostructured titanium surfaces followed by magnesium ion implantation for 30 minutes (Mg30) and hierarchical hybrid micro/nanostructured titanium surfaces followed by magnesium ion implantation for 60 minutes (Mg60) were used as test groups. The surface morphology, chemical properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 44 publications
0
37
2
Order By: Relevance
“…Plasma immersion ion implantation (PIII), a non-line-of-light technique (in which the path of propagation of energetic doping atoms is not obscured by obstacles) for surface doping, may be a good pathway for local delivery of magnesium onto implantable medical devices. Previously, Mg PIII-treated titanium has demonstrated good osteogenic properties mediated by local release of Mg ions 17 18 . However, less is known about the immunomodulatory effects of Mg PIII treatment.…”
mentioning
confidence: 99%
“…Plasma immersion ion implantation (PIII), a non-line-of-light technique (in which the path of propagation of energetic doping atoms is not obscured by obstacles) for surface doping, may be a good pathway for local delivery of magnesium onto implantable medical devices. Previously, Mg PIII-treated titanium has demonstrated good osteogenic properties mediated by local release of Mg ions 17 18 . However, less is known about the immunomodulatory effects of Mg PIII treatment.…”
mentioning
confidence: 99%
“…Although ICIE16-BG shows a superior ability to induce osteogenic differentiation on a cellular level in this study, its weaker ability to support the formation of the ECM might be improved by adding appropriate ions to the basic ICIE16-BG composition. Possible candidate ions are, amongst others, zinc, which stimulates protein production in osteoblasts [24,37], or magnesium, which promotes mineralization of the ECM and has been proven to enhance gene expression patterns of OCN and OPN [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the lack of bioactivity and osteoinductivity, a minimum of 3 months is required to achieve sufficient osseointegrated fixation after implantation [4,5]. Many efforts to modify the implant surface have demonstrated that the coating of the implant with bioactive chemical elements could functionalize the surface and accelerate osseointegration [68]. Among these elements, strontium (Sr) has similar characteristics to calcium [9,10], which enables Sr to deposit into the mineral phase of bone.…”
Section: Introductionmentioning
confidence: 99%